Using WordPress as a library content management system - Jones, Kyle M. L; Jones, Kyle M. L.; Farrington, Polly-Alida. (Chicago, IL ALA TechSource, 2011)
Authors Kyle M.L. Jones and Polly-Alida Farrington, along with several librarian contributors, deliver a richly illustrated, practical guide for using WordPress as a tool for managing digital content, from basic set-up to customization with plugins
Includes bibliographical references
Keywords: WordPress (Electronic resource).; Library Web sites -- Design; Library Web sites -- Management; Library science -- Blogs; Librarians -- Blogs; Blogs -- Design; Blogs -- Management; Web sites -- Authoring programs; Web site development; Libraries and the Internet; Library science -- Technological innovations; Electronic books